The critical role of physical frailty and function on depressive symptoms among community-dwelling older adults in China: A cross-sectional study - Wang, Qun; Song, Dan; Lin, Qiuru; Tao, An; Zhang, Yao; Li, Xilin; Qiu, Xichenhui (Frontiers in Psychiatry, 2023)
Introduction: With rapid population aging in China, geriatric depression has imposed a heavy burden on public health and society. This study aimed to investigate the prevalence and influencing factors of depressive symptoms among community-dwelling older adults in China. The findings of this study will contribute to the early detection and effective interventions for older adults with depressive symptoms. Methods: A cross-sectional study was conducted among people aged ≥ 65 years old in urban communities in Shenzhen, China, in 2021. This study assessed depressive symptoms (Geriatric Depression Scale-5, GDS-5), physical frailty (FRAIL Scale, FS), and physical function (Katz index of independence in the Activities of Daily Living, ADL). Multiple linear regression was used to examine potential predictors of depressive symptoms. Results: A total of 576 participants aged 71.73±6.41 years were included in the analysis. More than half of them were females (53.0%). The average score of GDS-5 was 0.57±1.11, with 78 (13.61%) participants with depressive symptoms (≥ 2). The mean scores of FS and ADL were 0.80±1.08 and 9.49±1.67, respectively. The final regression model indicated that those who were living alone, less satisfied with their personal life, frailer, and with worse abilities in ADL had a higher level of depression symptoms (R2 = 0.406, p< 0.001). Conclusion: The prevalence of depressive symptoms is high in this urban community-dwelling older adults in China. Given the critical role of frailty and ADL on depressive symptoms, specific attention to psychological support should be paid to older adults who are living alone and with poor physical conditions.